Best prognostic factor of neuroendocrine tumors: Grade or Stage? A multidisciplinary single-center study - Özaslan, Ersin; Bayram, Fahri; Karaca, Halit; Gürsoy, Şebnem; Öztürk, Figen; Sözüer, Erdoğan; Abdurrezzak, Ümmühan; Yurci, Alper; Can Sezgin, Gülten; Yıldırım, Afra; Başpınar, Osman; Kula, Mustafa; et al. (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Currently, there is no definite consensus about the prognostic factors of neuroendocrine tumors (NETs). We evaluate epidemiology, survival and especially prognostic factors in NETs. Materials and Methods: Patients who had a NET and were diagnosed between 2000 and 2014 at a tertiary care center were included. Demographic data, tumor characteristics and survival rates were evaluated, retrospectively. Results: Two-hundred and thirty-three patients (123 male, 110 female; median age, 55 years [16–92 years]) took part in the study. Primary NET sites were the lung (n=56), stomach (n=50), pancreas (n=39), colorectal (n=21), small intestine (n=19), and appendix (n=19). According to the NET classification by the WHO in 2010, 60% (n=140) of patients were grade-1, 15% (n=35) were grade-2, and 25% (n=58) were grade-3. According to TNM staging, 88 patients (37.8%) were stage I, 30 patients (12.8%) were stage II, 22 patients (9.5%) were stage III, and 93 patients (39.9%) were stage IV. Univariate analysis revealed significant associations between gender, age, grade, lymph node metastasis, distant metastasis, stage, and the number of organs impacted by metastases and overall survival. However, with multivariate analysis only age greater than 55 years, advancing grade, and inoperable tumors were significantly associated with shortened survival. Five-year survival was 81% in grade-1, 34% in grade-2, and 9% in grade-3 NETs. Conclusion: This study is the most comprehensive study in Turkey that has evaluated NETs using a multidisciplinary approach. Also, we suggest that age, operability and especially grade rather than stage are the most important prognostic factors in NETs.